SIMPLE EEG ASSESS WORKING MEMORY PROCESS IN DIFFERENCE GENDER - Fifi Veronica; Hanna Gunawan; Lulu L Fitri; Aldi Fernando; Galih Nadhova; Hilsa Hilsa (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Terminology working memory often used to describe the whole process of structure in memory, including executive function, which all information retains and uses in temporary period. Simple EEG, like Headband Muse Electroencephalography (EEG) which used 4 sensors EEG is one of the tools in neuroscience research to investigate neuronal process in different condition, as well as working memory process in simple and easiest way. Results in this study hopefully provide baseline data for another neurofeedback research in cognitive process. Material & Methods using the Muse, simple EEG as portable low cost and wireless two-channel EEG headband, we record 23 students at 4th grade elementary school in Jatinangor. The ? brain waves bands were recorded while they get memory span task, which had sequences base 1, read 1, interphase1, recall 1, base 2, read 2 interphase2, recall 2. EEG recorded result difference between gender. Oscillation ? brain wave will loaded into MATHLAB. In this study, we report sex related changes ? trends bands in EEG power as peak frequency for both frontal and temporoparietal sites, in several condition task in working memory process. In male participants increasing trends for ? in working memory process higher than female students. The result also stated asymetri frontal cortex and decreasing power of ? wave between TP and AF. We discuss our finding probability sex related chages their attentional and emotional in working memory process. Encoding process and retrieval also probability influence.